1997
DOI: 10.1055/s-2007-996131
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Thrombin Inhibitor Argatroban in Acute Cerebral Thrombosis

Abstract: Argatroban is a direct antithrombin agent developed for the first time by Okamoto et al in 1978. Unlike heparin, it manifests its anticoagulant effect by binding directly to the active site of thrombin. A phase II double-blind comparative study was conducted in 52 facilities with a placebo control. The drug was administered by a slow intravenous infusion at 60 mg/d for the first 2 days and then at 10 mg twice daily for the subsequent 5 days. Glycerol was used concomitantly as a basic therapy for both the argat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(44 citation statements)
references
References 7 publications
0
42
0
2
Order By: Relevance
“…Briefly, the characteristics of the Japanese Guidelines for the Management of Stroke 2004 can be summarized as follows: (1) it is the first evidence-based guideline for stroke treatment in Japan and the East; (2) it was produced by the Joint Committee on Guidelines for the Management of Stroke with the cooperation of 5 stroke-related societies in Japan; (3) it was developed jointly by neurologists, stroke internists, neurosurgeons, rehabilitation specialists, and clinical epidemiologists; (4) no financial support was accepted from any company; (5) it provides comprehensive coverage of all types of stroke in the acute and chronic stages, including prevention; (6) it is not a translation of stroke guidelines from the West, but rather a new guideline for the treatment of Japanese people, developed by Japanese doctors, and taking into consideration the evidence from the Japanese language literature, as well as the local situation in Japan; (7) novel pharmaceutical treatments so far approved only in Japan, but for which only one randomized controlled trial dealing with a rather small number of subjects [7][8][9] was available, were tentatively assigned recommendation grade B; (8) original classifications based on global standards were used for evidence levels and recommendation grades; (9) an evidence level was assigned to all the cited literature; and (10) an attempt was made to clarify what evidence is lacking in each field of stroke.…”
Section: Representative Characteristics Of the Japanese Guidelinesmentioning
confidence: 99%
“…Briefly, the characteristics of the Japanese Guidelines for the Management of Stroke 2004 can be summarized as follows: (1) it is the first evidence-based guideline for stroke treatment in Japan and the East; (2) it was produced by the Joint Committee on Guidelines for the Management of Stroke with the cooperation of 5 stroke-related societies in Japan; (3) it was developed jointly by neurologists, stroke internists, neurosurgeons, rehabilitation specialists, and clinical epidemiologists; (4) no financial support was accepted from any company; (5) it provides comprehensive coverage of all types of stroke in the acute and chronic stages, including prevention; (6) it is not a translation of stroke guidelines from the West, but rather a new guideline for the treatment of Japanese people, developed by Japanese doctors, and taking into consideration the evidence from the Japanese language literature, as well as the local situation in Japan; (7) novel pharmaceutical treatments so far approved only in Japan, but for which only one randomized controlled trial dealing with a rather small number of subjects [7][8][9] was available, were tentatively assigned recommendation grade B; (8) original classifications based on global standards were used for evidence levels and recommendation grades; (9) an evidence level was assigned to all the cited literature; and (10) an attempt was made to clarify what evidence is lacking in each field of stroke.…”
Section: Representative Characteristics Of the Japanese Guidelinesmentioning
confidence: 99%
“…The Ministry of Health Labour, and Welfare of Japan approved argatroban in patients with stroke according to the following schedule: argatroban infused continuously at a dose of 60 mg/d for the first 2 days, followed by twice daily infusion, at a dose of 10 mg over 3 hours, for 5 days. 4,5,11 …”
Section: Use Of Argatroban For Acute Ischemic Stroke In Japanmentioning
confidence: 99%
“…2 To the best of our knowledge, there are only 3 randomized controlled trials on argatroban use in patients with acute ischemic stroke: 1 from North America 3 and 2 from Japan. 4,5 These studies suggested that argatroban was effective and safe for the use as early anticoagulant therapy in acute ischemic stroke. However, the sample sizes of these studies were small.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…51,52 In Japan only, argatroban is also licensed for treatment of ischemic complications in patients with chronic peripheral arterial occlusions and for treatment of patients with ischemic stroke. 53,54 Argatroban has also been evaluated in several small, randomized, controlled trials in patients with acute coronary syndromes, but results were inconclusive. [55][56][57] …”
Section: Clinical Trials With Argatrobanmentioning
confidence: 99%